A review on the mechanical performance of three-dimensional warp interlock woven fabrics as reinforcement in composites. (February 2022) - Li, Mengru; Wang, Peng; Boussu, François; Soulat, Damien
In recent years, the research interest on three-dimensional warp interlock woven fabrics (3DWIFs) as reinforcement in composites is warranted and obtained popularity due to their advantages over two-dimensional laminated fabrics. The current literature tends to address the aspects of mechanical properties of 3DWIFs by experimental and numerical approaches. This review aims at providing an overview and comprehensive understanding of dry 3DWIFs. The filaments/yarns used, the common structures, and categories of 3DWIFs are reviewed. Recent characterizations of the mechanical performance of dry 3DWIFs are discussed. Theoretical and numerical models for predicting the mechanical properties of dry 3DWIFs are also delineated. The critical review can provide valuable ideas and guidance for future studies.